2016
DOI: 10.1183/13993003.01794-2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease exacerbation and inhaler device handling: real-life assessment of 2935 patients

Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) can be prevented by inhaled treatment. Errors in inhaler handling, not taken into account in clinical trials, could impact drug delivery and minimise treatment benefit. We aimed to assess real-life inhaler device handling in COPD patients and its association with COPD exacerbations.To this end, 212 general practitioners and 50 pulmonologists assessed the handling of 3393 devices used for continuous treatment of COPD in 2935 patients. Handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
235
4
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(270 citation statements)
references
References 13 publications
11
235
4
9
Order By: Relevance
“…Finally, as our questionnaire assessed actual treatment and not just prescription, adherence to treatment could influence the proportion of patients with maintenance treatment. Yet, adherence and correct inhaler technique have been reported to be equal between sexes [32] or even better in men [33,34] and subsequently should not explain our results. In summary, more research in sex differences and its implications for therapy is obviously needed [35,36].…”
Section: Discussionmentioning
confidence: 62%
“…Finally, as our questionnaire assessed actual treatment and not just prescription, adherence to treatment could influence the proportion of patients with maintenance treatment. Yet, adherence and correct inhaler technique have been reported to be equal between sexes [32] or even better in men [33,34] and subsequently should not explain our results. In summary, more research in sex differences and its implications for therapy is obviously needed [35,36].…”
Section: Discussionmentioning
confidence: 62%
“…Targeting inhaled drug formulations to the peripheral airways is not efficient, with most of the formulations being deposited in the central airways. Reducing the mean particle size of the inhaled drug increases the fraction reaching the peripheral areas of the lung [111]. Meta-analysis of RCTs demonstrated that extra-fine ICS have significantly higher odds of achieving asthma control with lower exacerbation rates at significantly lower doses than fine-particle ICS [120].…”
Section: Clinical and Device Preference Comparisons Of New Versus Oldmentioning
confidence: 99%
“…To our knowledge, the drop in delivered dose resulting from actuation of Turbuhaler or Easyhaler in a non-upright manner has not been reported, with the exception of one study that described an 8% drop resulting from horizontal actuation of the Turbuhaler [16]. However, reports of several studies of inhaler technique have underscored the importance of holding the Turbuhaler upright [6, 7, 11, 1720]…”
Section: Discussionmentioning
confidence: 99%
“…Many patients in routine clinical practice do not use their inhalers correctly. This may be due to a lack of training or inappropriate device choice, and poor inhaler technique correlates with both poor control of symptoms and increased exacerbations [5–7]. In addition, approximately 50% of adults and children do not take their medications as prescribed [5].…”
Section: Introductionmentioning
confidence: 99%